(untitled) (TAJ: Journal of Teachers Association, 2019)
Background: Tuberculosis (TB) is the one of the leading cause of death globally, more marked in developing countries like Bangladesh. The prevalence of Diabetes Mellitus (DM) is increasing globally fueled by obesity endemic. The study is designed to get an idea about prevalence and clinical impact of DM among pulmonary TB patients. Objective: The aim of the study is to find out the rate and effect of Diabetes mellitus in patients with pulmonary Tuberculosis. Material and Methods: This was a cross sectional study conducted in DOTS (directly observed therapy, short course) corner, outpatient department (OPD), Dhaka Medical College & Hospital, Dhaka from July to December 2012. 125 patients of pulmonary Tuberculosis were included in this study as case. 125 age and sex matched controls who were not suffering from pulmonary Tuberculosis were taken from the attendant of the patients who had given the consent. Prevalence and clinical impact of diabetes mellitus was sort out in both case and control group and compared with each other. Results: The study shows the prevalence of DM among pulmonary TB patients is 26.4% and among normal population (non TB patients) is 20.8%. The relative risk (odds ratio) of DM among pulmonary TB patients is 1.27 times more than non TB person with p-value - 0.02, which is significant. In symptoms analysis, diabetic patients have got more haemoptysis (45%), in contrast to non-diabetic group (13%), with p-value-0.001. In non-diabetic patients Fever are more common, 88% in contrast to diabetic group 57%, p-value-0.001. Sputum positivity is more common (69%) among diabetic pulmonary TB patients than non diabetic pulmonary TB patients (58%). On chest X ray findings this study reveals that pulmonary TB patient with DM having cavitary lesion is 33% while it is only 9.76% in non-diabetic persons. Conclusion: This study found that there was greater prevalence of DM among pulmonary TB patients (26.4%) than non pulmonary TB persons (20.4%). This findings provides the information that health care provider should intensively search presence of DM in pulmonary TB patients. TAJ 2019; 32(1): 46-53